Management of myopia in children and adolescents – Guidelines of the Polish Society of Ophthalmology - Bakunowicz-Łazarczyk, Alina; Modrzejewska, Monika; Szaflik, Jerzy; Filipek, Erita; Hautz, Wojciech; Urban, Beata (Klinika Oczna / Acta Ophthalmologica Polonica, 2024)
Myopia remains the leading cause of distance vision impairment globally. A recent landmark publication estimates that half of the world’s population will have myopia by 2050. The authors of the Guidelines present the possibilities for the treatment of progressive myopia in children and adolescents.